Analysis of online gambling crime prevention policies according to positive law and Islam in Indonesia - Susantyo, Herdy Pratama; Abdillah, Gadman Futor; Sanhaji, Mochammad Taufik; Romzi, Muhammad; Erfandi, Muhammad (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
The development of information technology, especially the internet, has had a significant impact on various aspects of human life, including the increasing prevalence of online gambling in Indonesia. This research aims to analyze the policies for combating online gambling crimes based on positive law in Indonesia and the perspective of Islamic law. Using a normative legal method with a library approach, this research analyzes legislation, academic journals, and related legal literature. The research results show that although Indonesia has regulated online gambling through the Criminal Code (KUHP) and the Electronic Information and Transactions Law (ITE), the existing policies still face challenges in terms of implementation and supervision. The rapid development of technology and the cross-border nature of online gambling are the main obstacles in addressing the issue. In the perspective of Islamic law, online gambling is considered haram because it contains elements of speculation and harms society. Therefore, the Islamic legal approach emphasizes prevention, education, and rehabilitation. The recommendations put forward include updating regulations to be more responsive to new technologies, enhancing law enforcement capacity, and strengthening rehabilitation programs for offenders. This research is expected to contribute to the development of more effective policies in addressing online gambling in Indonesia.